The Coronavirus and financial stability - Arnoud W. A. Boot; Elena Carletti; Rainer Haselmann; Hans-Helmut Kotz; Jan Pieter Krahnen; Loriana Pelizzon; Stephen M. Schaefer; Marti G. Subrahmanyam (Leibniz Institute for Financial Research SAFE, 2020)
The spreading of the Covid-19 virus causes a reduction in economic activity worldwide and may lead to new risks to financial stability. The authors draw attention to the urgency of the targeted mitigation strategies on the European level and suggest taking coordinated action on the fiscal side to provide liquidity to affected firms in the corporate sector. Otherwise, virus-related cashflow interruptions could lead to a new full-blown banking crisis. Monetary policy measures are unlikely to mitigate cash liquidity shortages at the level of individual firms. Coordinated action at European level is decisive to prevent markets from losing confidence in the resilience of banks, particularly in countries with limited fiscal capacity. In contrast to the euro crisis of 2011, the cause of the current crisis does not lie in the financial markets; therefore, the risk of moral hazard for banks or states is low.
Keywords: 330; coronavirus; financial stability; banking; strategies